Primary care consultation rates among people with and without severe mental illness: a UK cohort study using the Clinical Practice Research Datalink. Issue 12 (16th December 2015) - Kontopantelis, Evangelos; Olier, Ivan; Planner, Claire; Reeves, David; Ashcroft, Darren M; Gask, Linda; Doran, Tim; Reilly, Siobhan
Abstract : Objectives: Little is known about service utilisation by patients with severe mental illness (SMI) in UK primary care. We examined their consultation rate patterns and whether they were impacted by the introduction of the Quality and Outcomes Framework (QOF), in 2004. Design: Retrospective cohort study using individual patient data collected from 2000 to 2012. Setting: 627 general practices contributing to the Clinical Practice Research Datalink, a large UK primary care database. Participants: SMI cases (346 551) matched to 5 individuals without SMI (1 732 755) on age, gender and general practice. Outcome measures: Consultation rates were calculated for both groups, across 3 types: face-to-face (primary outcome), telephone and other (not only consultations but including administrative tasks). Poisson regression analyses were used to identify predictors of consultation rates and calculate adjusted consultation rates. Interrupted time-series analysis was used to quantify the effect of the QOF. Results: Over the study period, face-to-face consultations in primary care remained relatively stable in the matched control group (between 4.5 and 4.9 per annum) but increased for people with SMI (8.8–10.9). Women and older patients consulted more frequently in the SMI and the matched control groups, across all 3 consultation types. Following the introduction of the QOF, there was an increase in the annual trend of face-to-face consultation for people with SMI (average increase of 0.19 consultations per patient per year, 95% CI 0.02 to 0.36), which was not observed for the control group (estimates across groups statistically different, p=0.022). Conclusions: The introduction of the QOF was associated with increases in the frequency of monitoring and in the average number of reported comorbidities for patients with SMI. This suggests that the QOF scheme successfully incentivised practices to improve their monitoring of the mental and physical health of this group of patients.